2014
DOI: 10.1016/j.applthermaleng.2014.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Drop-in energy performance evaluation of R1234yf and R1234ze(E) in a vapor compression system as R134a replacements

Abstract: This paper presents an energy performance evaluation of two low-GWP refrigerants, R1234yf and R1234ze(E), as drop-in replacements for R134a. Tests are carried out in a monitored vapour compression system combining different values of evaporation and condensation temperature, and without/with the adoption of an internal heat exchanger. The parameters analysed are volumetric efficiency, cooling capacity and COP and they are presented taking R134a as baseline. Results show that without IHX the average volumetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(92 citation statements)
references
References 31 publications
5
81
0
6
Order By: Relevance
“…They measured 2-13% reduction in capacity but COP increments from 7 to 33% in relation to R-134a. Also, Mota-Babiloni et al (2014) using an open-type compressor measured reductions in capacity from 9 to 39% and reductions in COP from 6 to 7% regarding the operation with R-134a with the substitutes R-1234yf and R-1234ze(E). Finally, concerning large systems, Cabello et al (2017) analysed the R-134a drop-in process with R-152a in the primary circuit of a HFC/CO 2 cascade, obtaining similar energy behaviour than with R134a.…”
Section: Table 1 R-134a Drop-in Substitutes For Medium Temperature Amentioning
confidence: 99%
“…They measured 2-13% reduction in capacity but COP increments from 7 to 33% in relation to R-134a. Also, Mota-Babiloni et al (2014) using an open-type compressor measured reductions in capacity from 9 to 39% and reductions in COP from 6 to 7% regarding the operation with R-134a with the substitutes R-1234yf and R-1234ze(E). Finally, concerning large systems, Cabello et al (2017) analysed the R-134a drop-in process with R-152a in the primary circuit of a HFC/CO 2 cascade, obtaining similar energy behaviour than with R134a.…”
Section: Table 1 R-134a Drop-in Substitutes For Medium Temperature Amentioning
confidence: 99%
“…They also reported that the compressor discharge temperature of R1234yf is 16.4-17.3% lower than that of R134a. Mota-Babiloni et al [8] determined that the coefficient of performance (COP) and cooling capacity of R1234yf compared to R134a was up to 3-11% and 9% lower, respectively. On the other hand, Lee and Jung [3] obtained 2.7% lower COP and 4.0% lower cooling capacity.…”
Section: Introductionmentioning
confidence: 99%
“…HFO refrigerants are actually unsaturated HFC refrigerants and widely recognized [13] as the next generation of refrigerants because of their environmental friendliness, costeffectiveness, and greater energy efficiencies. HFOs are distinguished from HFCs by being derivatives of olefins rather than alkanes (paraffins).…”
Section: Introductionmentioning
confidence: 99%